Meso-subtituted anionic metalloporphyrin catalysts immobilized on ionic liquid-functionalized mesoporous silica in oxidation of trimethylphenol - Roslan, Nurliana (2018)
Synthetic metalloporphyrins have been extensively studied as biomimetic models for cytochrome P-450 oxidative enzymes in catalysis of different substrates. Despite the advantages of superior activity and selectivity, as well as mild reaction temperatures, difficulties in catalyst recovery and purification of products still constitute the major drawbacks of homogeneous processes. This research aimed to develop new heterogeneous catalysts of meso-tetra-(4-sulfonatophenyl)porphyrinato metal complexes (MTSPP) immobilized in ionic liquid-functionalized mesoporous silica SBA-15. Hence, positively charged ionic liquid, 1-methyl-3-(3- triethoxysilylpropyl) imidazolium chloride (C3mimCl, denoted as ImIL) was explored as an interface linker for immobilization of the anionic MTSPP complexes onto the mesoporous silica support by electrostatic interactions. A series of ImILfunctionalized SBA-15 (ImIL@SBA) materials with different loadings of ImIL (1.0- 10.0 mmol) were prepared via the post-synthesis covalent grafting method. The immobilization of MTSPP complexes on the ImIL@SBA with different MTSPP loading (5, 10 and 25 μmol) was carried-out via the post-synthesis ion-exchange method to afford the MTSPP-ImIL@SBA (M: Mn, Fe, Cu and Zn) nanocomposites. The TGA results showed the relative stability of the MTSPP-ImIL@SBA catalysts decreased in the order of strength of metal ion binding: Cu(II) > Mn(II) > Zn(II) > Fe(II), which correlated directly with metal core electronegativity effect. The DRUV-Vis spectroscopy confirmed that FeTSPP could form iron porphyrin μ-oxodimeric species upon immobilization onto the surface of mesoporous silica support, which would cause the thermal stability of FeTSPP-ImIL@SBA to become very low. The catalytic properties of MTSPP-ImIL@SBA was tested in the one-step oxidation of 2,3,6-trimethylphenol (TMP) to 2,3,5-trimethylbenzoquinone (TMBQ) as a model reaction. Factors influencing the reaction were studied systematically, and a possible reaction mechanism was then proposed. The catalytic activity trend of the MTSPPImIL@ SBA increased in the order of metal ion: Cu(II) > Mn(II) > Zn(II) > Fe(II). Under the optimum condition, CuTSPP-ImIL@SBA showed excellent performance with 80-100% conversions of TMP and 100% selectivity for TMBQ. Furthermore, MTSPP-ImIL@SBA catalysts were highly stable and reusable up to four cycles without a significant loss of activity, with a high TON value of 1302 after 24 hours and TOF up to 54 h-1, which were readily attainable under mild reaction conditions. As a conclusion, the cationic ImIL linker in the MTSPP-ImIL@SBA seemed to play a pivotal role in the catalytic mechanism by enhancing the chemical stability of the anionic MTSPP complexes. Therefore, the MTSPP-ImIL@SBA nanocomposites emerged as potential heterogeneous catalysts for the production of TMBQ, the chemical intermediate for the industrial production of Vitamin E.